Inclusionary housing : creating and maintaining equitable communities - Jacobus, Rick (Lincoln Institute of Land Policy, 2015)
This report illustrates how local governments can realize the full benefit of inclusionaryhousing policies, which require developers of new market-rate real estate to providesome affordable units for lower-income residents. Policy makers, practitioners, and localleaders will learn how to build public support, use data to inform program design, establish reasonable expectations for developers, and ensure long-term program quality.
Keywords: Inclusionary housing programs -- United States.; Housing policy -- United States.; Low-income housing -- United States.; Mixed-income housing -- United States.; Affordable housing -- United States.; Programmes de logement inclusif -- États-Unis.; Logement -- Politique gouvernementale -- États-Unis.; Pauvres -- Logement -- États-Unis.; Mixité sociale dans le logement -- États-Unis.; BUSINESS & ECONOMICS -- Infrastructure.; SOCIAL SCIENCE -- General.; Housing policy; Inclusionary housing programs; Low-income housing; Mixed-income housing; United States